Corn nutrition and yield as a function of boron rates and zinc fertilization - Nogueira, Lais Meneghini [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Megda, Marcio Mahmoud; Galindo, Fernando Shintate [UNESP]; Buzetti, Salatier [UNESP]; Alves, Cleiton Jose [UNESP] (Univ Estadual Londrina, 2019)
Brazilian Cerrado soils are commonly deficient in boron (B) and zinc (Zn). It is still debated whether B and Zn interaction has a synergistic or antagonistic effect on the absorption thereof. Thus, we conducted this study to evaluate the effect of boron rates (0, 1, 2, 3, and 4 kg ha(-1), as boric acid), with or without zinc fertilization (2 kg ha(-1) Zn, as zinc sulfate), on corn nutritional status and grain yield. We also assessed the residual effect of such fertilization on the fall corn crop grown on an Oxisol in a no-tillage system. A synergistic effect between B and Zn was observed on corn nutritional status when applied to the soil at rates of up to 2 kg ha(-1), with higher soil contents resulting from the interaction between these micronutrients. Zinc fertilization and increasing boron rates had no significant influence on corn grain yield in both spring/summer and fall crops, grown on a boron-deficient, clayey soil of Cerrado biome.
Keywords: Borated fertilizer; Boric acid; Micronutrients; Nutrient concentrations; Zea mays L.